Comment on “Atomic mass compilation 2012” by B. Pfeiffer, K. Venkataramaniah, U. Czok, C. Scheidenberger - Audi, Georges; Blaum, Klaus (Atomic data and nuclear data tables, 2015)
In order to avoid errors and confusion that may arise from the recent publication of a paper entitled “Atomic Mass Compilation 2012”, we explain the important difference between a compilation and an evaluation; the former is a necessary but insufficient condition for the latter. The simple list of averaged mass values offered by the “Atomic Mass Compilation” uses none of the numerous links and correlations present in the large body of input data that are carefully maintained within the “Atomic Mass Evaluation”. As such, the mere compilation can only produce results of inferior accuracy. Illustrative examples are given.
Gesehen am 28.07.2020